Wound care using metronidazole in a patient with diabetic foot ulcer: a case report - Agus Santosa; Okta Fajar Silviana; Neneng Khasanah (Proceedings Series on Health & Medical Sciences, 2020)
The control of infection in diabetic foot ulcers is essential to prevent injuries from getting worse. Infection in diabetic foot ulcers is generally caused by bacteria existence in the wound. Antibiotics may not be orally able to exterminate bacteria rapidly in the wound area, so antibiotics are needed directly and topically to the wound to reduce the infection process. This case describes wound care intervention using gauze added by antibiotic metronidazole as a wound compress in a 46-year-old male patient with diabetic foot ulcers treated at Cempaka Ward Banyumas Regional Public Hospital. This case is interesting because the medical intervention given to patients is rarely implemented in clinical practice. The conclusion is that a metronidazole antibiotic used to compress wounds in patients with diabetic foot ulcers can reduce the wound infection process.